Rządy Polemona II i Antiocha IV w Cylicji Trachejskiej - Kozłowski, Jakub (Studia Europaea Gnesnensia, 2011)
The aim of the article is to demonstrate the significance of transformations in Cilicia Trachea, initiated with the rule of Antioch IV and Polemon II, and the impact their activities had on the introduction of direct administration in these areas by Vespasian.